Child with Deletion 9p Syndrome Presenting with Craniofacial Dysmorphism, Developmental Delay, and Multiple Congenital Malformations. (25th July 2013) - Sirisena, Nirmala D.; Wijetunge, U. Kalpani S.; de Silva, Ramya; Dissanayake, Vajira H. W.
Abstract : A 4-month-old Sri Lankan male child case with a de novo terminal deletion in the p22→ pter region of chromosome 9 is described. The child presented with craniofacial dysmorphism, developmental delay, and congenital malformations in agreement with the consensus phenotype. A distinctive feature observed in this child was complete collapse of the left lung due to malformation of lung tissue. Cytogenetic studies confirmed terminal deletion of the short arm of chromosome 9 distal to band p22 [46, XY, del(9)(p22→ pter)]. This is the first reported case of a de novo deletion 9p syndrome associated with pulmonary hypoplasia. This finding contributes to the widening of the spectrum of phenotypic features associated with deletion 9p syndrome.